2015
DOI: 10.1007/s40502-015-0159-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of osmotic stress on osmolyte accumulation and ammonia assimilating enzymes in chickpea cultivars

Abstract: An investigation was conducted to evaluate the effect of osmotic stress on four chickpea cultivars, viz., two drought tolerant (ICC 4958 and Vijay), and two drought susceptible (JG-216 and PG 1808) subjected to mild (-0.4 MPa) and severe (-1.2 MPa) osmotic stress induced by PEG-6000. The activity of ammonia assimilation enzymes, viz., nitrate reductase (NR) glutamine synthetase (GS), glutamate synthase (GOGAT) decreased, while activity of proline synthesizing enzyme D 1 pyrroline-5-carboxlate synthetase (P 5 C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 11 publications
4
5
0
Order By: Relevance
“…The significant accumulation of phenolic compounds in tissues of drought tolerant plants and their powerful ROS scavenging roles indicate their roles against the oxidative damage caused by drought and salt stress ( Reginato et al, 2015 ). Some previous reports also confirmed the contributions of different osmolytes in inducing drought tolerance in various crops ( Tan et al, 2006 ; Farooq et al, 2009 ; Pawar et al, 2015 ).…”
Section: Discussionsupporting
confidence: 61%
“…The significant accumulation of phenolic compounds in tissues of drought tolerant plants and their powerful ROS scavenging roles indicate their roles against the oxidative damage caused by drought and salt stress ( Reginato et al, 2015 ). Some previous reports also confirmed the contributions of different osmolytes in inducing drought tolerance in various crops ( Tan et al, 2006 ; Farooq et al, 2009 ; Pawar et al, 2015 ).…”
Section: Discussionsupporting
confidence: 61%
“…In addition, free proline in chickpea cvs. 'ICC4958' and 'Vijay' grown under -1.2 MPa PEG-induced osmotic stress increased by 1.37 and 1.34 folds, relating to stimulate P5CS (Δ 1 -pyrroline-5-carboxylate synthetase, a rate-limiting enzyme for proline biosynthesis) activity for 133.7% and 122.1% over control, respectively (Pawar et al, 2015). Likewise, free proline osmolyte in sorghum seedlings cvs.…”
Section: Discussionmentioning
confidence: 98%
“…Many enzymes are involved in nitrogen metabolism, among which glutamine synthetase (GS; EC 6.3.1.2) and glutamate synthase (GOGAT) are very important for the production of amino acids and amides from inorganic nitrogen (N) [17]. Drought has been reported to restrict plant growth through enzymes inhibition implicated in N metabolism as well [15,20,21]. For instance, Pawar et al [20] demonstrated that drought stress leads to decreased nitrate reductase (NR), GS, and GOGAT enzyme activities.…”
Section: Introductionmentioning
confidence: 99%
“…Drought has been reported to restrict plant growth through enzymes inhibition implicated in N metabolism as well [15,20,21]. For instance, Pawar et al [20] demonstrated that drought stress leads to decreased nitrate reductase (NR), GS, and GOGAT enzyme activities. Inhibition of these enzymes increases the concentration of ammonium, which is toxic for plants; therefore, an increase in the ability of a plant to assimilate ammonium can improve stress tolerance [22].…”
Section: Introductionmentioning
confidence: 99%